Encyclopedia of archaeology - Pearsall, Deborah M. (Elsevier/Academic Press, 2008)
"Archaeology is a subject that fascinates us. From Egyptian tombs to a frozen Alpine wayfarer, from cities buried under volcanic ash to stone arrow heads turned up by the plow, archaeology is in the news and in our backyards. It is paradoxical that a subject that so easily captures the imagination is so difficult for the serious layman to access. Superficial media treatments and picture-book atlases and site guides on the one hand, jargon-heavy scholarly books and narrowly focused articles on the other-there are few ways to learn about the real world of archaeology outside the college classroom or the dig site. The Encyclopedia of Archaeology changes this, in making all aspects of archaeology accessible to a broad audience of the general scientific community, educators, students, and avocational archaeologists. Professional archaeologists and anthropologists will also find the encyclopedia a ready source of up-to-date information on specialities outside their own expertise. The Encyclopedia of Archaeology encompasses all aspects of archaeology, including the nature and diversity of archaeology as a scientific discipline, the practice of archaeology, archaeology in the everyday world, and the future of the discipline. Featured in the Encyclopedia of Archaeology are articles by leading authors that summarize archaeological knowledge at the beginning the 21st century, highlighting important sites and issues, and tracing the development of prehistoric cultures around the globe. No existing work provides the breadth and depth of coverage as the Encyclopedia of Archaeology"--Publisher description.